Race, rights, and rifles: the origins of the NRA and contemporary gun culture - Filindra, Alexandra (Chicago studies in American politics, 2023)
"One-third of American adults-some 86 million people-own firearms. This is not just for protection or hunting. Today it is common to associate US gun-centric ideology with individualist and libertarian traditions in American political culture, but Race, Rights, and Rifles shows that gun-centric ideology rests on a very old, but different foundation-a belief system dating back to the American Revolution that fuses republican notions of civic duty with a belief in white male supremacy and a commitment to maintaining racial and gender hierarchies. Alexandra Filindra calls this belief system ascriptive martial republicanism because it combines republican ideals of civic virtue with an exclusionary vision of citizenship and an emphasis on martial preparedness over other forms of civic participation and service. Drawing on wide-ranging historical and contemporary evidence, Race, Rights, and Rifles traces how this ideology emerged during the Revolution and became embedded in America's institutions, from state militias to the National Rifle Association (NRA). Although no longer a dominant ideology, ascriptive republicanism remains a potent force in American politics, and the NRA is a critical vector of its influence. New survey data shows that many White Americans -including those outside of the NRA's direct orbit-understand citizenship in ascriptive martial republican terms. This ideology is a robust predictor of gun ownership, support for the NRA, and beliefs that guns are a sign of good citizenship. Moreover, those who embrace this ideology are more likely than others to value gun rights over voting rights, to embrace antidemocratic norms, and to justify political violence"--